Tensile mechanical properties of CoCrFeNiTiAl high entropy alloy via molecular dynamics simulations. (March 2022) - Sun, Zhi Hui; Zhang, Jie; Xin, Gao Xin; Xie, Lu; Yang, Li Chun; Peng, Qing
Abstract: High-entropy alloys (HEAs) are a new type of multi-principal metal materials that exhibit excellent mechanical properties, good thermal stability, and high corrosion resistance, with versatile potential applications. In this paper, we have investigated CoCrFeNi(Al0.3 Ti0.2 )x HEA with different Ti and Al contents using XRD, tensile testing, and molecular dynamics simulations. The effects of Ti and Al contents and temperature on the mechanical properties were also explored. The experimental results showed that the CoCrFeNi(Al0.3 Ti0.2 )x HEAs were mainly composed of the FCC matrix phase and γ′ phase (Ni3 (Al, Ti)) after rolling and annealing. The addition of Ti and Al induced the formation of high-temperature strengthening phases in the CoCrFeNi HEA, which significantly improved the mechanical properties. The molecular dynamics simulations also indicates that the elastic modulus and tensile strength of CoCrFeNi(Al0.3 Ti0.2 )x HEA are steadily improved with the Ti and Al addition. The tensile strength increases with the dislocation density. Besides, we have performed a high-temperature mechanical characterization of the CoCrFeNiAl0.225 Ti0.15 HEA. The experimental data have revealed that the material's strength continuously declines with stretching temperature, opposed to that of toughness. The high-temperature tensile modulus of elasticity decreases with the temperature. Temperature also diminishes the tensile strength due to the average reduction of the dislocation density. Highlights: The CoCrFeNi(Al0.3 Ti0.2 )x HEAs were mainly composed of the FCC matrix phase and γ′ phase (Ni3 (Al, Ti)) after rolling and annealing. The addition of Ti and Al induced the formation of high-temperature strengthening phases, significantly improved the mechanical properties. MD simulations indicates that the elastic modulus and tensile strength steadily improved with the Ti and Al addition.